Autoimmune inflammation as a key risk factor for heart failure with preserved ejection fraction: the different types of inflammation driving to HFpEF - Gremese, Elisa; Bruno, Dario; Perniola, Simone; Ceolan, Jacopo; Ferraccioli, Gianfranco (Frontiers in Medicine, 2025)
ImportanceHeart failure with preserved ejection fraction (HFpEF), defined by an ejection fraction >50%, has emerged as the most prevalent form of heart failure at the community level. Multiple comorbidities, including diabetes, hypertension, obesity, atrial fibrillation, renal diseases, and autoimmune conditions, have been linked to its development. These conditions share common pathways involving oxidative stress, metabolic dysregulation, ischemia, and a chronic inflammatory milieu.ObservationsPatients with autoimmune diseases such as rheumatoid arthritis (RA), systemic lupus erythematosus (SLE), and systemic sclerosis (SSc) exhibit an increased risk of developing HFpEF, often through mechanisms involving chronic inflammation and endothelial dysfunction, which precede the clinical manifestation of HFpEF. Clinical studies have demonstrated that the risk of developing HFpEF exists independently of traditional cardiovascular risk factors, underscoring the pivotal role of chronic inflammation and autoimmunity as key contributors to its pathogenesis.Conclusions and relevanceThe translational implication is that the distinct inflammatory pathways driving these autoimmune diseases (e.g., myeloid-T cells and T-B cell-mediated inflammation in RA, and B cell-driven inflammation in SLE and SSc) should become personalized therapeutic targets to prevent HFpEF progression. Early intervention with novel therapies, such as sodium-glucose cotransporter type 2 (SGLT2) inhibitors, could be crucial in managing these patients during the early disease stages. Additionally, the H2FPEF score should be routinely employed to facilitate early diagnosis and risk stratification, providing a robust framework for personalized management strategies.